Genome-wide screening of cytogenetic abnormalities in multiple myeloma patients using array-CGH technique: a Czech multicenter experience - Smetana, Jan; Frohlich, Jan; Zaoralova, Romana; Vallova, Vladimira; Greslikova, Henrieta; Kupska, Renata; Nemec, Pavel; Mikulasova, Aneta; Almasi, Martina; Pour, Ludek; Adam, Zdenek; Sandecka, Viera; et al. (BioMed research international, 2014)
Characteristic recurrent copy number aberrations (CNAs) play a key role in multiple myeloma (MM) pathogenesis and have important prognostic significance for MM patients. Array-based comparative genomic hybridization (aCGH) provides a powerful tool for genome-wide classification of CNAs and thus should be implemented into MM routine diagnostics. We demonstrate the possibility of effective utilization of oligonucleotide-based aCGH in 91 MM patients. Chromosomal aberrations associated with effect on the prognosis of MM were initially evaluated by I-FISH and were found in 93.4% (85/91). Incidence of hyperdiploidy was 49.5% (45/91); del(13)(q14) was detected in 57.1% (52/91); gain(1)(q21) occurred in 58.2% (53/91); del(17)(p13) was observed in 15.4% (14/91); and t(4;14)(p16;q32) was found in 18.6% (16/86). Genome-wide screening using Agilent 44K aCGH microarrays revealed copy number alterations in 100% (91/91). Most common deletions were found at 13q (58.9%), 1p (39.6%), and 8p (31.1%), whereas gain of whole 1q was the most often duplicated region (50.6%). Furthermore, frequent homozygous deletions of genes playing important role in myeloma biology such as TRAF3, BIRC1/BIRC2, RB1, or CDKN2C were observed. Taken together, we demonstrated the utilization of aCGH technique in clinical diagnostics as powerful tool for identification of unbalanced genomic abnormalities with prognostic significance for MM patients.
Keywords: dospělí; srovnávací genomová hybridizace; Female; Genome-Wide Association Study; Adult; ženské pohlaví; lidé; mnohočetný myelom; Aged, 80 and over; prognóza; Male; chromozomální aberace; Aged; Czech Republic; celogenomová asociační studie; nádorové proteiny; Neoplasm Proteins; Comparative Genomic Hybridization; Prognosis; Česká republika; lidé středního věku; senioři nad 80 let; Multiple Myeloma; senioři; mužské pohlaví; Middle Aged; Chromosome Aberrations; Humans